PERANAN PENYIDIK PEGAWAI NEGERI SIPIL BALAI BESAR PENGAWASAN OBAT DAN MAKANAN DALAM MEMBERANTAS TINDAK PIDANA PEREDARAN OBAT TRADISIONAL ILEGAL DIPEKANBARU - Retti Masitta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Pekanbaru is the capital of one of the provinces in Indonesia, which is strategically locatedadjacent to one of the neighboring countries and cities that have the highest population inIndonesia. Such as currency, where the city of Pekanbaru is staregis this, which is not utilizedby the party responsible for the crime, one of which health crime. Especially traditional crimeof illegal drug trafficking with the intent to make a profit with the illegal circulation oftraditional drugs without obtaining marketing authorization from the FDA. To combat thecrime, it requires the role of Civil Servant Center for Food and Drug Administration isoperating according to the Criminal Procedure Code and Law No. 36 Year 2009 on Health.Role of Civil Servant Center for the Food and Drug Administration had not been optimal.This is because there are still many obstacles faced by civil servants investigator Great Hallof the Food and Drug Administration.Keywords: Role, PPNS BBPOM, Combat, Circulation, Traditional Illegal Drugs.